2005
DOI: 10.1016/j.amjhyper.2005.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Outcome in Treated Hypertensive Patients with Responder, Masked, False Resistant, and True Resistant Hypertension

Abstract: This study shows that patients with masked hypertension are at higher risk than those with responder hypertension, and that those with false resistant hypertension are at lower risk than those with true resistant hypertension. Ambulatory BP monitoring should be performed in treated hypertensive patients to obtain a better prognostic stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
186
0
19

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(227 citation statements)
references
References 29 publications
8
186
0
19
Order By: Relevance
“…19 After adjustment for serum cholesterol, smoking, and diabetes mellitus, sustained hypertension (hazard ratio: 2.94; 95% CI: 1.49 to 5.82) and MH (hazard ratio: 2.77; 95% confidence interval: 1.15 to 6.68) were independent predictors of cardiovascular morbidity when compared with normotensive subjects. 19 Other studies with 24-hour ABP monitoring 36,58 and home BP 28,29,35,59 confirmed the excess risk of events in subjects with MH as compared with subjects with normal values of office and out-of-office BP.…”
Section: Masked Hypertensionmentioning
confidence: 86%
“…19 After adjustment for serum cholesterol, smoking, and diabetes mellitus, sustained hypertension (hazard ratio: 2.94; 95% CI: 1.49 to 5.82) and MH (hazard ratio: 2.77; 95% confidence interval: 1.15 to 6.68) were independent predictors of cardiovascular morbidity when compared with normotensive subjects. 19 Other studies with 24-hour ABP monitoring 36,58 and home BP 28,29,35,59 confirmed the excess risk of events in subjects with MH as compared with subjects with normal values of office and out-of-office BP.…”
Section: Masked Hypertensionmentioning
confidence: 86%
“…In a population of 18 036 patients, those with resistant hypertension were found to have a 47% increased rate of death and cardiovascular disease (defined as all-cause mortality and incident cardiovascular events (non-fatal MI, congestive heart failure, stroke or chronic kidney disease (CKD))) compared with those with non-resistant hypertension. Another study by Pierdomenico et al 15 examined the prognosis of resistant hypertension in 742 patients, excluding those with white coat resistant hypertension. They demonstrated an increased rate of cardiovascular disease events of 2.9 times (compared with controlled hypertensive individuals) but this study was unable to account for patients who were pseudoresistant due to non-adherence.…”
Section: Introductionmentioning
confidence: 99%
“…In hypertensive patients with white-coat effect (difference in CBP that is ≥20/10 mm Hg greater than ABP/HBP), the ABP/HBP recordings should be the preferred modality of long-term monitoring. Conversely, masked hypertension (where CBP is normal, but ABP/HBP is elevated) also carries an increased risk of adverse cardiovascular outcomes 28. Utilisation of ABP/HBP would be necessary to guide antihypertensive treatment for those with masked hypertension.…”
Section: Diagnosis/initiation Of Treatmentmentioning
confidence: 99%